Role of Phosphate and Other Proton-Donating Anions in Respiration-Coupled Transport of Ca(2+) by Mitochondria - Lehninger, Albert L. (1974)
Measurements of extra oxygen consumption, (45)Ca(2+) uptake, and the osmotic expansion of the matrix compartment show that not all permeant anions are capable of supporting and accompanying the energy-dependent transport of Ca(2+) from the medium into the matrix in respiring rat-liver mitochondria. Phosphate, arsenate, acetate, butyrate, β-hydroxybutyrate, lactate, and bicarbonate + CO(2) supported Ca(2+) uptake, whereas the permeant anions, nitrate, thiocyanate, chlorate, and perchlorate, did not. The active anions share a common denominator, the potential ability to donate a proton to the mitochondrial matrix; the inactive anions lack this capacity. Phosphate and the other active permeant anions move into the matrix in response to the alkaline-inside electrochemical gradient of protons generated across the mitochondrial membrane by electron transport, thus forming a negative-inside anion gradient. It is postulated that the latter gradient is the immediate “pulling” force for the influx of Ca(2+) on the electrogenic Ca(2+) carrier in respiring mitochondria under intracellular conditions. Since mitochondria in the cell are normally exposed to an excess of phosphate (and the bicarbonate-CO(2) system), particularly in state 4, inward transport of these proton-yielding anions probably precedes and is necessary for inward transport of Ca(2+) and other cations under biological conditions. These observations indicate that a negative-inside gradient of phosphate generated by electron transport is a common step and provides the immediate motive power not only for (a) the inward transport of dicarboxylates and tricarboxylates and (b) the energy-dependent exchange of external ADP(3-) for internal ATP(4-) during oxidative phosphorylation, as has already been established, but also for (c) the inward transport of Ca(2+), K(+), and other cations.